The cryptochristians : Klostoi those who returned, Tenesur those who have changed - Ανδρεάδης, Γεώργιος (Κυριακίδη Αφοι, 1995)
A valuable and very moving work which describes the life and sufferings of “Cryptochristians" in the Ottoman Empire. These people were living “neomartyrs”. Includes the story of “Papa-Nicholas” Planas and his family.